How consumer involvement influences beer flavour preferences. Issue 4 (27th April 2020) - Calvo-Porral, Cristina; Rivaroli, Sergio; Orosa-Gonzalez, Javier
Abstract : Purpose: Much of the innovation in the beer sector has focussed on flavour, resulting in a proliferation of flavoured beers. In this paper, the understanding of consumers' flavour preferences is a relevant question for the beer industry; however, little is known whether consumer involvement influences beer flavour preferences, and the purpose of the present study is directed to shed light on this area yet under-investigated. Design/methodology/approach: The research was conducted in Spain, where a total amount of 565 beer consumers were classified based on their level of involvement with beer. Data were analysed by analysis of variance, Tukey test, principal component analysis and multidimensional scaling (MDS) to examine consumers' preferences for different beer flavours using a consumer hedonic approach based on like and dislike evaluation. Findings: The findings support the existence of a homogeneous pattern in beer-flavour preferences, regardless of consumer involvement, showing a greater liking for conventional flavours. Further, highly involved consumers show a higher preference for unconventional or flamboyant beer flavours, than low or medium involved consumers. Originality/value: Derived from the findings it can be stated that consumers do not accept all kinds of flavours and that their level of product involvement affects their flavour preferences.